2006
DOI: 10.1097/01.hco.0000198981.48013.70
|View full text |Cite
|
Sign up to set email alerts
|

Selective site ventricular pacing

Abstract: Selective site pacing holds promise in attempting to reduce the problems associated with chronic ventricular pacing. Large, prospective, randomized control trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
(102 reference statements)
0
19
0
Order By: Relevance
“…As an alternative strategy, RV outflow tract pacing has been performed, [9][10][11] whereas its procedure may be considered to be associated with a high threshold and low sensing. 18) Additionally, the anatomical accuracy for RV outflow tract is poor and several reports have used inconsistent pacing sites: RV outflow tract free wall or septum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative strategy, RV outflow tract pacing has been performed, [9][10][11] whereas its procedure may be considered to be associated with a high threshold and low sensing. 18) Additionally, the anatomical accuracy for RV outflow tract is poor and several reports have used inconsistent pacing sites: RV outflow tract free wall or septum.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) Recently, selective site pacing (SSP), where alternate sites for ventricular pacing are used, has come into use to improve ventricular dyssynchrony. [9][10][11] In SSP, His-bundle or para-His pacing 12,13) and a procedure where a ventricular lead is positioned in the RV outflow tract have been used. [14][15][16] The former involves technical difficulties, whereas the latter has produced unsatisfactory longterm effects and also poses a high risk of complications such as pericardial effusion.…”
mentioning
confidence: 99%
“…3 Results of acute and chronic studies show mixed results with a tendency toward better hemodynamic outcome when pacing at these alternative sites. 4 However, much uncertainty is present, due to poor definition of the exact pacing site, the limited number of hemodynamic parameters studied, and nonrandomized studies. Of the 5 chronic studies referred to in Reference 4, 2 demonstrated a significant benefit of RV septal over RV apical pacing.…”
Section: Rv Apical Versus Rv Midseptal Pacingmentioning
confidence: 99%
“…Of the 5 chronic studies referred to in Reference 4, 2 demonstrated a significant benefit of RV septal over RV apical pacing. 4 In 1 of these studies, RV septal pacing produced a shorter QRS duration, whereas in the other positive study, the septum was mapped to achieve the shortest QRS duration. 25,26 In the present study, the lead was implanted in the RV midseptum, based solely on position and not optimizing the QRS complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation